Meeting Physical Activity Requirements by Gender in Six Native American Communities (P04-117-19) - Poirier, Lisa (Curr Dev Nutr, 2019)
OBJECTIVES: Physical activity can reduce the risk for non-communicable diseases (NCD), such as obesity and type-2 diabetes, which are higher in Native American (NA) populations than the general American population. It is worth exploring the physical activity (PA) levels of NA men and women to see if they met general requirements or differ because of the higher rates of NCDs in NA communities. METHODS: As part of the OPREVENT2 trial, 601 adult NA participants across six NA communities completed the International Physical Activity Questionnaire- Short Form (IPAQ-SF), which includes questions about walking, moderate and vigorous activity. Data were analyzed using the IPAQ guidelines to create a categorical variable of activity level based on weekly total MET-minutes including truncating extreme values, leaving 586 participants. METs are multiples of a person's metabolic resting rate and help capture intensity. Based on the total MET-minutes per week, participants were broken into two categories, insufficiently active (IA) and sufficiently active (SA). RESULTS: Based on self-reported IPAQ-SF questions for walking, moderate, and vigorous activity, 71.2% of men (n = 116) and 77.3% of women (n = 327) met the requirement for being SA. Men in the SA category reported an average of 3713 MET-minutes per week compared to an average of 2818 MET-minutes per week for women, which was significantly higher (P = 0.0001). There were several men who had very high total MET-minutes per week due to the self-reported frequent and long session of vigorous activity. CONCLUSIONS: While NA men may exercise for a significantly longer total amount of time during a week, a higher percentage of women were considered sufficiently active. Future physical activity education and interventions should focus on getting more NA men to exercise and focus on duration and intensity of exercise for NA women. FUNDING SOURCES: National Heart, Lung, and Blood Institute R01.